2018
DOI: 10.1038/s41598-018-19474-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of silver nanocolloids on plant complex type N-glycans in Oryza sativa roots

Abstract: Silver nanomaterials have been mainly developed as antibacterial healthcare products worldwide, because of their antibacterial activity. However, there is little data regarding the potential risks and effects of large amounts of silver nanomaterials on plants. In contrast, N-glycans play important roles in various biological phenomena, and their structures and expressions are sensitive to ambient environmental changes. Therefore, to assesse the effects of silver nanomaterials, we focused on the correlation bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…For example, a recent study reported a high abundance of PMGs (76.7% of the N ‐glycome) in ungerminated Oryza sativa seeds, which decreased dramatically to 36.1% after 48 h of germination (Horiuchi, Hirotsu, & Miyanishi, ). The PMGs were proposedly carried by vacuolar‐resident storage proteins utilised for growth and development during germination (Horiuchi et al ., ), and were further suggested to be synthesised and preserved in the rice germ until germination (Ying et al ., ). These findings suggest that GnT‐I, Hex and the other glyco‐enzymes facilitating PMP synthesis in plants (see Section II.1 a ) are active during seed development.…”
Section: Surveying Pmps Across the Eukaryotic Kingdoms And Phylamentioning
confidence: 99%
“…For example, a recent study reported a high abundance of PMGs (76.7% of the N ‐glycome) in ungerminated Oryza sativa seeds, which decreased dramatically to 36.1% after 48 h of germination (Horiuchi, Hirotsu, & Miyanishi, ). The PMGs were proposedly carried by vacuolar‐resident storage proteins utilised for growth and development during germination (Horiuchi et al ., ), and were further suggested to be synthesised and preserved in the rice germ until germination (Ying et al ., ). These findings suggest that GnT‐I, Hex and the other glyco‐enzymes facilitating PMP synthesis in plants (see Section II.1 a ) are active during seed development.…”
Section: Surveying Pmps Across the Eukaryotic Kingdoms And Phylamentioning
confidence: 99%
“…Glycoconjugates are widely present in animal [78], as well as plant [79][80][81][82][83] and microbial [84][85][86][87] structural and functional systems [88]. Many of the plant glycan antigens are on the cell wall [89,90].…”
Section: Glycans Are Ubiquitousmentioning
confidence: 99%